PENAFSIRAN MUFASSIR DAN FEMINIS MUSLIM TERHADAP AYAT-AYAT AL-QUR`AN YANG BERWAWASAN GENDER - Nurjannah Ismail (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
This article critically investigates the interpretation of some mufassirs (al-Qur’an interpreters) and moslem feminists about women affairs in sura al-Nisa’; some of other things are that of the origin of women creation, the leadership in the house dan polygamy. The significance of this investigation is to look critically at the thoughts of the mufassirs to find out their interpretation about al-Qur’an verses, which are apparently discriminatory towards women, and to discover the similarities and the differences between them in interpreting the same verses. This research was purely library research, and the analysis method used was the combination of inductive and comparative ones by using hermeneutic approach. From this research, it was found that in ad- dition to their similar interpretation, there are many different and controversial points of view among the mufassirs due to several factors like their background of thinking, socio-religious status, the methodology used, and the existence of bias in interpreting the texts.